KOMUNIKASI DALAM PENDIDIKAN ANAK - Nurma Yunita Yunita; Irni Latifa Irsal (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2021)
This study aims to determine how communication is applied by Luqman in educating his children stated in QS. Luqman verses 12-19, by of showing styles, methods, theories, materials and characteristics of parents or educators in educating their children or students. Therefore it can be a reference in communicating with children in achieving educational goals. This research is a content analysis research using the tahlili method, namely the interpretation method which explains the content of the verses of the Qur'an from all its aspects. The results of this study are: First, the educational material in Surah Luqman is about monotheism or the prohibition of associating partners with Allah, being safe or believing that every action must have a reward, morality to parents, human beings and morality to the environment. Second, the criteria for educators in QS. Luqman are patient, sincere, knowledgeable and pious and Third, Educational Communication Methods in Surah Luqman verses 12-19 are the advice method, the exemplary method and the habituation method.